PTSD, stigma and barriers to help-seeking within the UK Armed Forces. Issue 4 (18th December 2014) - Murphy, Dominic; Busuttil, Walter
Abstract : Among the general public, much is known about the longer-term consequences of not seeking support for mental health difficulties. However, within military populations, and in particular, the UK Armed Forces, less is known. Understanding the factors that present barriers for UK service personnel with mental health difficulties accessing support is important because this may provide a means for support personnel to seek help sooner. This paper explores the literature relating to the impact of untreated post-traumatic stress disorder (PTSD) among military personnel, attempts to draw conclusions about the barriers that may prevent personnel seeking help and the efficacy of previous interventions to address these. Stigma has been highlighted as the key barrier to help-seeking behaviours, in particular, internal stigma, which can be classified as negative beliefs about the self that an individual may hold as a result of experiencing symptoms of PTSD.